PRICE BEHAVIOUR IN INDIA'S COCONUT SECTOR - DR. PRAFULLA K. DAS (International Coconut Community Journal, 1991)
Coconut being a smallholder perennial crop, studies on the price behaviour of its products require serious consideration. A cursory look into the price structures of coconut, copra and coconut oil reveal that the price fluctuations are not only infrequent, but also most violent. The seasonal indices show different patterns for different products. The Compound Growth Rates of wholesale prices for coconut products are found to be around 10 per cent per annum between 1970 and 1989. The indices however suggest that the relative prices in coconut sector are declining even though the absolute prices show significant growths. The correlation coefficients (r) between wholesale prices of coconut products are assessed as, 0.99. The analysis of price behaviours in the important coconut product markets further reveals that those markets are highly competitive. Attempts have been made to predict the prices of copra with the use of coconut oil prices; and the prices of coconut with the use of prices of either copra or coconut oil in the same market or in different markets. The prediction models are found out to be very good fit with the value of r2 ranging between 0.98 and 0.99.